Deregulated transcription factors in cancer cell metabolisms and reprogramming. (November 2022) - Kant, Rajni; Manne, Rajesh Kumar; Anas, Mohammad; Penugurti, Vasudevarao; Chen, Tingjin; Pan, Bo-Syong; Hsu, Che-Chia; Lin, Hui-Kuan
Abstract: Metabolic reprogramming is an important cancer hallmark that plays a key role in cancer malignancies and therapy resistance. Cancer cells reprogram the metabolic pathways to generate not only energy and building blocks but also produce numerous key signaling metabolites to impact signaling and epigenetic/transcriptional regulation for cancer cell proliferation and survival. A deeper understanding of the mechanisms by which metabolic reprogramming is regulated in cancer may provide potential new strategies for cancer targeting. Recent studies suggest that deregulated transcription factors have been observed in various human cancers and significantly impact metabolism and signaling in cancer. In this review, we highlight the key transcription factors that are involved in metabolic control, dissect the crosstalk between signaling and transcription factors in metabolic reprogramming, and offer therapeutic strategies targeting deregulated transcription factors for cancer treatment.